O ensino de geografia para alunos com deficiência visual: novas metodologias para abordar o conceito de paisagem - Arruda, Luciana Maria Santos de (2014)
The present dissertation was developed from the need to rethink the teaching of geography to visually impaired students concerning the landscape concept. In order to do that the main goal was the creation of sensory didactic material using the experiences lived by the students of Instituto Benjamin Constant (IBC) in the landscape that composes it. It was also necessary a reflection on special and inclusive education in the world and in Brazil, particularly nowadays in Brazil with an inclusive perspective in which legislation has advanced greatly. To present IBC and how it organizes itself as a center of reference was also of the utmost importance, as it is necessary a historical recovery of the teaching of geography in this centenarian and pioneer institution, due to the fact that the first tactile didactic materials used in the teaching of these students were there. The methodology used by teachers is a differential from the moment that several languages are employed to develop the teaching of geography in the IBC, and through their accounts this knowledge was presented and recovered. Geography is build up from learning experiences that go beyond the classroom and therefore the use of sensory didactic resources will add up to the teaching and learning process making the construction of a multisensory landscape possible. Thus, by means of sensory activities, materials which may help students in the understanding of the landscape concept were devised, making the use of the senses real. The theoretical reference was based on Tuan (2012) and Soler (1999) to think this multisensory landscape. Therefore, to think of a meaningful geographic education, independent of the student and the reality that surrounds him, is very important in an inclusive society.